(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper highlights the results of experimental work done to evaluate the applicability of recycled aggregates in the production of fresh concrete. Three sets of concrete mixes undertaken for study are fresh concrete, recycled aggregate concrete and recycled aggregate concrete with MicroSilica as admixture. All mixes were designed for characteristic strength of M.20.Compressive strength of of concrete cubes was tested for 7 and 28 days. The effect of admixture (MicroSilica)on recycled aggregate concrete was studied. Compressive strength of frsh concrete(FAC), recycled aggregate concrete(RAC) and recycled aggregate concrete with admixture(RACA) are compared after 7 and 28 days. It is observed that the strength achieved by the recycled aggregate concrete with the addition of MicroSilica is better than the normal fresh concrete. So this study justifies the applicability of recycled aggregates in the production of fresh concrete using MicroSilica as admixture.